2007
DOI: 10.1007/s11605-007-0160-9
|View full text |Cite
|
Sign up to set email alerts
|

Review Article: Appendicitis In Groin Hernias

Abstract: To review the clinical presentation, outcome and causes of acute appendicitis presenting within a groin hernia. A comprehensive review of the past 70 years of English language surgical literature was conducted pertaining to acute appendicitis presenting within an inguinal or femoral hernia. Thirty-four reports describing 45 patients were reviewed to determine age, position, gender, pathologic stage at presentation, causal suppositions, and clinical outcomes. Hernial appendicitis presented as an inguinal absces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
48
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 35 publications
2
48
0
2
Order By: Relevance
“…Computer Tomography with Multi Planar Reconstruction is the most useful technique, to better visualize the appendix and its relationship with surrounding structures, thus aiding in confidently making the correct diagnosis pre-operatively [7]. Management depends on the state of the appendix, majority of authors agree that a normal appendix within the hernial sac does not require appendectomy [8,9]. In neonates with underlying appendicitis, herniotomy and appendicectomy should be performed [9,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Computer Tomography with Multi Planar Reconstruction is the most useful technique, to better visualize the appendix and its relationship with surrounding structures, thus aiding in confidently making the correct diagnosis pre-operatively [7]. Management depends on the state of the appendix, majority of authors agree that a normal appendix within the hernial sac does not require appendectomy [8,9]. In neonates with underlying appendicitis, herniotomy and appendicectomy should be performed [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Management depends on the state of the appendix, majority of authors agree that a normal appendix within the hernial sac does not require appendectomy [8,9]. In neonates with underlying appendicitis, herniotomy and appendicectomy should be performed [9,10]. In adults the repair of the hernia should be performed with Bassini or Shouldice techniques, without making use of synthetic meshes or plugs within the defect due to the high risk of suppuration of such materials [10].…”
Section: Discussionmentioning
confidence: 99%
“…Several cases of abscess in the hernial sac caused by acute appendicitis or by strangulation and perforation of the intestines in the hernial sac have been reported [2,3] . The protrusion of a vermiform appendix into the inguinal hernial sac, termed an Amyand hernia, and into the femoral hernial sac is termed a De Garengeot hernia [4,5] .…”
Section: Discussionmentioning
confidence: 99%
“…The protrusion of a vermiform appendix into the inguinal hernial sac, termed an Amyand hernia, and into the femoral hernial sac is termed a De Garengeot hernia [4,5] . When acute appendicitis occurs in the hernial sac, it may lead to the development of a hernial sac abscess [3] . However, our review of the literature revealed that, after cases of abscess in the hernial sac secondary to peritonitis were reported by Cronin and Ellis in 1959 and Chary in 1977 [1,6] , few other such cases have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Most of them are present in an Amyand's hernia, as it is an entity which aVects mainly older patients with a median peak age of 69 years [5].…”
mentioning
confidence: 99%